Relationships between type of pain and work participation in people with long-standing spinal cord injury: results from a cross-sectional study. Issue 5 (May 2018) - Roels, Ellen; Reneman, Michiel; Stolwijk-Swuste, Janneke; Laake-Geelen, Charlotte; Groot, Sonja; Adriaansen, Jacinthe; Post, Marcel
Abstract Study design Multicentre, cross-sectional study. Objectives To describe the relationships between the presence of (different types of) pain and participation in paid work in people with long-standing spinal cord injury (SCI). Furthermore, the associations of pain-related work limitations, age, gender, relationship, education, lesion level, and time since injury (TSI) with work participation (WP) were investigated. Setting The Netherlands. Methods Individuals (n = 265) with SCI for ≥ 10 years were included. Data were collected through a structured consultation with a rehabilitation physician and self-report questionnaire. Descriptive statistics and logistic regression analysis were performed. Results Median age of participants was 47.9 years, median time since injury was 22 years, 73% were male, 69% had complete SCI and 59% had paraplegia, 50% had paid work, 63% reported musculoskeletal pain, 49% reported neuropathic pain, and 31% reported other pain. Self-reported pain-related work limitations were significantly (V = 0.26 andV = 0.27) related to WP. In bivariable logistic regression analyses, no statistically significant relationships between type of pain and WP were observed. Younger age (OR=0.96), male gender (OR=0.52), a stable relationship (OR = 1.70), and shorter time since SCI (OR = 0.97) were significantly associated with a higher chance of being employed. Multivariable analysis confirmed these findings and in addition showed a higher level of education to be positively related with WP. Conclusion Age, gender, relationship, education, TSI and self-reported work limitations showed a relationship with WP. Different types of pain were unrelated to WP. Sponsorship Fonds NutsOHRA through the Dutch Organization for Health Research and Development (ZonMw), Project number 89000006.